The pop-up research centre – Challenges and opportunities. (October 2019) - Toomey, R.J.; McEntee, M.F.; Rainford, L.A.
Abstract: Objectives: This article sets out to describe the concept of the "pop-up" research centre as a means to promote and develop radiography research locally, nationally and internationally, and to empower professional colleagues to set up similar initiatives in the future. Key findings: A detailed overview of the development and management of "pop-up" research is provided based on the experiences of the authors, including specific examples. Matters such as study design, approvals, equipment and software, environment, participant recruitment and management, research teams and activity costs are discussed. Quantifiable benefits of "pop-up" research such as resultant peer reviewed publications, development of researchers' skills and potential collaborations are described. A number of "soft skill" benefits are also apparent and include enhanced organisational profiles, team building and the development of leadership skills. Conclusions: "Pop-up" research centres are a valuable option for conducting research and offer the radiography profession an achievable mechanism to increase and enhance research activity. However, careful planning and execution are essential.